Congenital chylothorax - Özkan, Hasan; Ay, Naim; Özaksoy, Dinç; Erçal, Derya; Erata, Yakup; Durak, Hatice; Evyapan, Özcan; Toprak, Suphi (The Turkish Journal of Pediatrics, 1996)
Congenital chylothorax is a rare condition in which chyle accumulates in the pleural space because of an intrauterine obstruction or anomalies of the thoracic duct. This paper presents a case of congenital chylothorax diagnosed antepartum echographically. The patient’s history revealed a previous sibling with a similar diagnosis. The baby developed respiratory distress after delivery and the diagnosis was established by thoracentesis. Computed tomography of the chest and nuclear lymphangiography were obtained to evaluate the origin of the pleural effusion, but a congenital fistula or other pathology of the thoracic duct could not be demonstrated. Management of the baby consisted of ventilatory support in the delivery room, repeated thoracentesis and thoracostomy tube drainage, total parenteral nutrition and formula containing medium-chain triglycerides. The infant was discharged six weeks after birth in good condition.